2022
DOI: 10.3390/ijerph19095414
|View full text |Cite
|
Sign up to set email alerts
|

The Linkage between Ethical Leadership, Well-Being, Work Engagement, and Innovative Work Behavior: The Empirical Evidence from the Higher Education Sector of China

Abstract: In this study, we investigate the relationship between ethical leadership (EL), work engagement (WE), well-being, and innovative work behavior (IWB). The significance of these variables has increased in the current era when the influence of technology is exponentially increasing in the education sector. We investigate the role of ethical leadership in determining innovative work behavior. Moreover, we investigate the moderating effect of WB in the relationship between EL and WE. We also examine the mediating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 67 publications
7
14
0
1
Order By: Relevance
“…Vivid positive effects of EL were noted in the results, which shows consensus with prior studies in this context (e.g., Atik and Celik, 2020 ; Farmanesh and Zargar, 2021 ; Zhou et al, 2021 ; Jia et al, 2022 ). It was also noted in the literature that positive attributes of leaders can lead to notable positive attitudes toward the job and the organization ( Amundsen and Martinsen, 2015 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Vivid positive effects of EL were noted in the results, which shows consensus with prior studies in this context (e.g., Atik and Celik, 2020 ; Farmanesh and Zargar, 2021 ; Zhou et al, 2021 ; Jia et al, 2022 ). It was also noted in the literature that positive attributes of leaders can lead to notable positive attitudes toward the job and the organization ( Amundsen and Martinsen, 2015 ).…”
Section: Discussionsupporting
confidence: 89%
“…As university teachers carry a number of responsibilities (e.g., teaching, exams, research, registration, and mentoring), provision of necessary tools and resources alongside organizational support and empowerment by their leaders become vital for their job satisfaction and performance outcomes that affect their wellbeing (Amundsen and Martinsen, 2015;Telyani et al, 2021;Zhou et al, 2021;Jia et al, 2022;Zaman et al, 2022). Job satisfaction of teachers is considered to be an emotional state toward work that entails subjective views, and attitudes toward the job itself (Zhou et al, 2021).…”
Section: Empowering Leadership and Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers found that ethical leadership increases work engagement (Jia et al, 2022). Ethical leaders create a work conducive environment through open communication (Babalola et al, 2016) and fair distribution of tasks (Wibawa & Takahashi, 2021) where followers feel more comfort in exerting efforts and dedication to complete the assigned tasks (Thiel et al, 2018).…”
Section: Ethical Leadership and Work Engagementmentioning
confidence: 99%
“…To do so, modern universities should develop the innovative work behaviors of academic staff by providing them strong ethical leadership, effective in respects, and organizational support so as to attain leading aims overwhelmed at anticipated success (Musenze & Mayende, 2022). Ethical leadership has gained attention in higher education sector as it is believed that ethical leaders improve productivity by valuing employees' rights and dignity (Jia, Zhu, Zhang, Rasool, Asghar & Chin, 2022).…”
Section: Introductionmentioning
confidence: 99%